1996
DOI: 10.1063/1.117314
|View full text |Cite
|
Sign up to set email alerts
|

Ion implantation induced enhancement of magnetoresistance in La0.67Ca0.33MnO3

Abstract: Thin films of colossal magnetoresistance (MR) material, La0.67Ca0.33MnO3, were implanted with different doses (1011–1015 ions/cm2) of 200 keV Ar+ ions. The implanted samples were examined by ion channeling and x-ray diffraction techniques. The channeling results clearly showed that the magnitude of the induced lattice disorder did not increase greatly for implantation doses up to 5×1013 ions/cm2. In this low dose implantation regime, the magnetoresistance {MR=[R(0)−R(H)]/R(0)} increased by 50%, the peak resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…The 10 13 ions/cm 2 implantation qualitatively reproduced that shown in Ref. 9. Of specific interest in this study was the observation that increasing the fluence further to 5 ϫ10 15 ions/cm 2 causes a peak in the resistance to reappear within our measurement window.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The 10 13 ions/cm 2 implantation qualitatively reproduced that shown in Ref. 9. Of specific interest in this study was the observation that increasing the fluence further to 5 ϫ10 15 ions/cm 2 causes a peak in the resistance to reappear within our measurement window.…”
supporting
confidence: 83%
“…Chen et al 9 implanted 200 keV Ar ϩ ions at fluence between 10 11 and 10 15 ions/cm 2 and found that the major influence of the implantation was to increase peak resistivity, and magnetoresistance, and decrease magnetoresitivity peak temperature. A detailed mechanism for these effects was not presented.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[25,26]. It is found that low energy (keV) ion implantation causes significant changes in the transport behaviour of manganites but since the ion remains in the film it has non-uniform depth profile in the film [27,28]. High energy oxygen ion irradiation of epitaxial LCMO thin film has been used to study the structural magnetization and magnetotransport properties.…”
Section: High T C Temperature Superconductorsmentioning
confidence: 99%
“…Since it is assumed 38 in the general case that the hopping distance a h is equal to a lattice constant, the noninteracting limit is quite justified for these doped manganites. For the value of dpa in this study (about In ion-irradiation experiments [16][17][18][19] much larger dpa values (up to 0.01 and more) have been produced which have resulted in an increase in resistance in the insulating paramagnetic state by one (and sometimes two) order of magnitude. This effect is accompanied by an increase in the activation energy E a (see Eq.…”
Section: Discussionmentioning
confidence: 99%